45.1: High‐Performance Deep Blue OLEDs with EQE up to 31%. (24th February 2021) - Li, Yilang; Li, Guomeng; Duan, Lian; Zeng, Lichang; Liu, Song
Abstract : The low efficiency of blue devices has been a bottleneck problem for OLED panel manufacturers for a long time. In recent years, TASF‐OLED has attracted great attention because of the high external quantum efficiency and color purity, which makes it a promising technology for high efficiency deep blue OLEDs. In this paper, we present our latest development of TADF material for deep blue TASF‐OLEDs with an emission peak at 460 nm and a high external quantum efficiency up to 31 %.